Chronic Disease Self-Management Program (CDSMP) in the Workplace: Opportunities for Health Improvement - Matthew Lee eSmith; Mark G. Wilson; David M. DeJoy; Heather M. Padilla; Heather eZuercher; Phaedra eCorso; Robert eVandenberg; Kate eLorig; Marcia G. Ory (Frontiers Media S.A., 2015)
.